A sexually dimorphic pattern of growth hormone secretion in the elderly. - Hindmarsh, P; Dennison, E; Pincus, S; Cooper, C; Fall, C; Matthews, DR; Pringle, P; Brook, C (1999)
In rodents, the sexually dimorphic pattern of pulsatile GH secretion is an important determinant of growth, liver enzyme function and insulin-like growth factor I (IGF-I) expression. Whether this difference is present in humans at different ages is unclear. We studied GH secretory patterns in the elderly by constructing 24-h serum GH profiles in 45 male and 38 female (age, 59.4-73.0 yr) volunteers and related patterns to IGF-I, IGF-binding protein-3 (IGFBP-3), and GH-binding protein levels; body mass index; and waist/hip ratio. Serum GH concentrations were measured in samples drawn at 20-min intervals and analyzed using a sensitive chemiluminescent assay (Nichols Institute Diagnostics: sensitivity, 0.036 mU/L). The 24-h serum GH profiles were analyzed using a concentration distribution method to determine GH peak and trough levels, spectral analysis, and assessment of serial irregularity by approximate entropy (ApEn). There was a highly significant difference in mean 24-h serum GH concentrations in females compared to males (males, 0.88 mU/L; females, 1.31 mU/L; P = 0.009) as a result of significantly higher trough GH levels (males, 0.04 mU/L; females, 0.16 mU/L; P < 0.001). Peak values were not significantly different. Serum IGF-I levels were significantly higher in males (males, 162.4 ng/mL; females, 87.8 ng/ mL; P < 0.001). Peak GH values were related to serum IGF-I levels (males: r = 0.39; P = 0.009; females: r = 0.5; P = 0.002), whereas trough GH levels were not. IGFBP-3 levels were similar and related to GH peaks only in males (r = 0.32; P = 0.03). GH was secreted with a dominant periodicity of 200 min in males and 280 min in females (P < 0.025). The proportion of time taken up by regular oscillatory activity was less in females (females, 11.1%; males, 14.7%; P = 0.01). GH secretion assessed by ApEn was more disordered in females (males, 0.60; females, 0.81; P < 0.001), and increasing disorder was associated with lower IGF-I levels. Body mass index was negatively related to GH in both sexes. In males, trough values were the major determinant (r = -0.31; P = 0.04), whereas in females, the peak value was the major determinant (r = 0.35; P = 0.04). Trough GH levels were inversely related in both sexes to waist/hip ratio (males: r = -0.40; P = 0.006; females: r = -0.44; P = 0.006) and to increasing secretory disorder (ApEn; r = -0.46; P < 0.001). These data demonstrate a sexually dimorphic pattern of GH secretion in the elderly.